Effect of Planting Periods on Growth and Development of Durum Wheat Cultivars Under Drought Conditions (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article presents the results of studies of sowing dates in dry farming conditions, as well as the development phases of durum wheat varieties. The activity of growth and development of varieties depending on the sowing period was studied.